Natural Nanominerals Show Enzyme-Like Activities. (8th July 2021) - Feng, Feng; Wang, Peixia; Zhang, Yihe; An, Qi; Lin, Yue; Tong, Wangshu; Chu, Paul K.; Liang, Minmin
Abstract : Natural nanominerals (NNMs) are progressively deposited during earth's formation. They have shown a broad range of applications from industrial catalysis, environmental treatment, and earth science to pharmaceutics due to their unique nanostructures and characteristics. Here, we first report that NNMs have intrinsic enzyme-like properties and show good biocompatibility. First, we characterized the morphology and structure of the six most representative NNMs including sepiolite, attapulgite, halloysite, montmorillonite, kaolinite, and diatomite by SEM, TEM, and XRD. Then, we quantitatively tested their peroxidase- (POD-), catalase- (CAT-), oxidase- (OXD-), and superoxide dismutase- (SOD-) like activities. The results indicate that different kinds of NNMs show varying degrees of POD-like, CAT-like, and SOD-like activities and minor OXD-like activity. Finally, we tested their cytotoxicity and found that the selected representative NNMs have no or less influence on cell viability, showing high biosafety. At present, NNMs have been widely used, mostly focusing on the physical and chemical properties, such as luminescence and conductivity. Our work promotes the understanding of NNMs, providing a new direction for the better application of NNMs.